Cooperation at a discount - Will I give away your money? - Johannes Lohse (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Will individuals contribute to a public good, even if doing so imposes a negative externality on an outsider? This paper describes the results of an experiment in which decision makers could contribute to a real public good, while (part of) the contribution costs were passed on to another participant. Decision makers with social preferences thus faced lower contribution cost but had to take into account additional costs imposed on an outsider. Such trade-offs are pervasive in many public good decisions, in which those who decide about provision, those who finance provision and those who benefit from it are different actors. My findings suggest that decision makers, at large, ignored adverse effects imposed on another participant. When varying both the distribution of initial endowments and the fraction of costs passed on to the outsider, I find that decision makers only refrain from contributing if the outsider has to pay for a disproportionate share or the full provision costs. This finding is best explained by advantageous inequity aversion.
Keywords: H41; C92; H23; 330